Benign pericholecystic regeneration mimicking hepatocellular carcinoma: a potential pitfall in imaging of cirrhosis. - Borhani, Amir A.; Patel, Naishal; Patel, Vedang; Haghshomar, Maryam; Grimaldi, Gregory; Miller, Frank H.; McGinty, Katrina (Abdominal Radiology, 2025)
Several pseudolesions mimicking malignancy have been reported in cirrhotic and non-cirrhotic livers. Pericholecystic regeneration is among those pseudolesions and can occasionally mimic malignancy. Herein we present a case series comprised of 10 cirrhotic patients (majority due to alcoholic liver disease [ALD] or metabolic dysfunction associated steatotic liver disease [MASLD]) with pericholecystic observations initially categorized as highly suspicious for HCC (LR-4 and LR-5) due to their suspicious enhancement pattern which were later proven to be benign based on biopsy, transplantation or imaging criteria (stability of size and morphology on serial CT or MRI for > 2 years). These observations ranged 2–6.3 cm in size, were multiple in most patients and universally resulted in indentations of gallbladder. Arterial phase hyperenhancement and washout, features usually attributed to hepatocellular carcinoma (HCC), were seen in most patients. However, ancillary features of malignancy such as diffusion restriction, increased T2 signal, and hypointensity on hepatobiliary phase MRI were not present. Pericholecystic observations, in particular in the setting of ALD and MASLD, should be carefully assessed and possibility of pseudolesion should be considered especially when the observations are multiple, cause indentation of gallbladder, and lack ancillary features of malignancy.